Práticas alimentares de gestantes e mulheres não grávidas: há diferenças? - Gomes, Caroline De Barros; Malta, Maíra Barreto; Martiniano, Ana Carolina De Almeida; Bonifácio, Luiza Pereira Di; Carvalhaes, Maria Antonieta De Barros Leite (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: To determine the eating behavior of pregnant women assisted by primary health care and to compare it with women at childbearing age in Brazilian capitals. METHODS: A cross-sectional study conducted on 256 pregnant women in the second trimester of gestation, selected by drawing lots from those assisted by primary health care units of a municipality in the state of São Paulo in 2009/2010. Eating habits were investigated via a questionnaire adapted from the VIGITEL system, consisting of questions about eating habits in general and the frequency and consumption characteristics of food groups/specific foods. For tis comparison, we used the indicators reported by the VIGITEL system for women at childbearing age in Brazilian capitals in 2010. The analyses involved the presentation of frequency distribution and descriptive statistics with comparisons according to the age group. RESULTS: Most patients had breakfast every day (86.7%) and 45.7% habitually exchanged a main meal for a snack once or twice a week. A daily consumption of fruit, raw salad and vegetables was not reported by 48.8%, 41.8% and 55.1% of the women, respectively. Fish was reported to never or almost never be consumed by 64.4% of the pregnant women. At least once a week, 69.9% of them reported the consumption of soda, and 86.4% of wafers/cookies. The comparison between the pregnant women and women at childbearing age in capitals showed a close similar prevalence of overweight, and no difference in the regular consumption of fruit and vegetables. Meat containing excess of fat and whole milk were more consumed by pregnant women, with differences reported in all the age groups analyzed. On the other hand, the pregnant women reported a less regular intake of soft drinks. CONCLUSIONS: The actions that need to be performed in prenatal care are various and very important, promoting the consumption of specific foods and providing guidelines about eating behavior, while reinforcing healthy eating habits already present.

OBJETIVOS: Conhecer o comportamento alimentar de gestantes assistidas pela atenção primária à saúde e compará-lo ao de mulheres em idade fértil das capitais brasileiras. MÉTODOS: Estudo transversal realizado no segundo trimestre gestacional com 256 gestantes, sorteadas dentre as assistidas pelas unidades de atenção primária à saúde de um município do interior paulista em 2009/2010. As práticas alimentares foram investigadas utilizando questionário adaptado do sistema Vigitel, composto por questões acerca de comportamentos alimentares em geral e frequência e características de consumo de grupos alimentares/alimentos específicos. Para a comparação foram utilizados os indicadores reportados pelo sistema Vigitel para as mulheres em idade fértil das capitais brasileiras no ano de 2010. As análises envolveram a apresentação de distribuição de frequências e estatísticas descritivas (distribuição de frequências ou médias e respectivos intervalos de confiança) com comparações de acordo com faixa etária. RESULTADOS: A maioria das gestantes consumia o café da manhã todos os dias (86,7%); a troca da refeição principal por lanche uma ou duas vezes por semana era o hábito de 45,7%. O consumo diário de frutas, salada crua, verduras e legumes não ocorria, respectivamente, em 48,8, 41,8 e 55,1% das gestantes. Peixe foi relatado como nunca ou quase nunca consumido por 64,4% das gestantes. Pelo menos uma vez por semana, 69,9% delas relataram consumo de refrigerante e 86,4% de bolacha/biscoito. Comparando as gestantes e mulheres em idade fértil das capitais brasileiras, a prevalência de excesso de peso foi bastante parecida e não houve diferenças entre o consumo regular de frutas e hortaliças. Carne com excesso de gordura e leite integral foram mais consumidos pelas gestantes, com diferenças em todas as faixas etárias analisadas. Por outro lado, gestantes tiveram menor ingestão regular de refrigerantes. CONCLUSÕES: Devem ser variadas e de grande importância as ações a serem praticadas na atenção pré-natal, desde promover o consumo de alimentos específicos até orientações sobre comportamentos alimentares, não deixando de reforçar os hábitos alimentares saudáveis já concretizados.
Eating habits of pregnant and non-pregnant women: are there differences?
Keywords: Prenatal nutrition; Pregnant women; Food habits; Women's health; Pregnancy; Nutrição pré-natal; Gestantes; Hábitos alimentares; Saúde da mulher; Gravidez